Healthcare Managers; Islamic Decision-making - Zohreh Mousavi Kashi; Arezou Sayad; Abolfazl Movafagh (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Decision-making is of paramount importance in personal, social, and organizational life, influencing both personal and organizational affairs. Indeed, all human's life is a chain of decisions made by him (1). In this regard, decision-making in major managements, particularly in health sector where lives of people as well as physical and spiritual health are involved, is of particular importance. For downloading the full-text of this article please click here.